Public administration, civic engagement, and spanish-speaking communities - Irizarry, José Luis (Public administration & social equity., 2025)
Public Administration, Civic Engagement, and Spanish-Speaking Communities builds on and develops ideas and issues discussed at the first bilingual (Spanish-English) special session at the National Academy of Public Administration's (NAPA) 2022 Social Equity Leadership Conference (SELC) hosted by the Masagung Graduate School of Management at the University of San Francisco. This book explores issues of social equity in public service for Spanish speaking communities and how these communities experience social inequities that negatively impact the creation and sustainability of their meaningful inclusion and democratic participation in civic and public life. This book addresses the lack of voices and perspectives from Spanish speaking communities in mainstream discourse and practice of social equity in public administration by inviting those voices to elucidate the issues, their contexts, and significance. Part 1 provides foundations and context in social equity, language access legislation and policies, English-Spanish translation and interpretation, nuances about the diversity of Spanish speaking communities as well as of the Spanish languages, the roles of the nonprofit sector and civil society organizations to compensate for market and government failures resulting in inequities, and relevant ethical considerations. Part 2 addresses communication, information, and disinformation (news, social media, and government communication). Part 3 addresses Hispanic/Latino intersectional identities and social equity including issues of race, gender, status, and the human service delivery. Part 4 examines specific topics in social equity (such as homelessness, healthcare, voting and civic engagement, criminal justice, and crisis recovery information). Part 5 provides a number of innovative applications, case studies, and teaching tools for students, academics, and practitioners.